PENGARUH DIVERSIFIKASI PRODUK, LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN SUMBER DAYA MANUSIA - Gillian Pauli Sibarani; Shanti Shanti (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2023)
This study seeks to reveal the relationship between product diversification, leverage, profitability, and company size on human resource disclosure. These variables were chosen since they were included as factors influencing disclosure on human resources. This study used quantitative research with hypothesis testing. This study used secondary data in the form of company data taken from the annual report of manufacturing companies listed on Indonesia Stock Exchange during the period of 2016-2019. Based on the predetermined criteria, the number of research samples used was 186 data. The data analysis technique in this study used multiple linearregression.The results showed that product diversification had a positive effect on human resources disclosure. Leverage has no effect on human resources disclosure. Profitability has a positive effect on human resources disclosure. Company size has no effect on human resources disclosure.